Embodied Energy and Carbon of Residential Buildings: Towards an Actual nZEB Concept - Moazzen, Nazanin; Ashrafian, Touraj (CLIMA 2022 conference, 2022)
Over the past few decades, energy efficiency policies have concentrated more on buildings' energy consumption and performance. EU established strategies by energy performance of buildings directive and its amendments for all new and retrofitted buildings to achieve nearly Zero Energy Buildings (nZEBs). Most of the studies and approaches cover the operation phase of the building life cycle, while, by observing the building's whole life cycle, it is determined that buildings are accounted for energy consumption during not just the operation phase and also the construction and demolishing stages. Consequently, the most prominent buildings should progress towards nearly Zero Energy Buildings by evaluating the energy consumption during the whole life cycle and not just during the operation. The embodied energy that covers the energy consumed in the process and manufacturing of the material, transportation, and installations on-site, is intensive energy consumed in a short period compared to the operation energy. Residential buildings are accounted for extensive energy consumption among different building typologies due to their size and number. According to various studies on residential buildings, in conventional and low energy buildings, the share of embodied energy has varied between 6 and 20%, and 26 and 57%, respectively. It means that embodied energy of the buildings is not negligible. Consequently, a logical method for residential buildings to reach the nZEB level using energy-efficient measures and proper materials considering the life cycle of buildings is inevitable. The paper aims to investigate the possibility of obtaining nearly zero energy levels in residential buildings reflecting the whole life cycle. The paper has concentrated not only on the operation energy but also on the embodied energy and carbon commencing from applying various measures to the building. The embodied energy and carbon data for building materials have been obtained from the Intergovernmental Panel on Climate Change (IPCC) database. All primary energy consumption of the building and improvement measures during the operation phase are computed with dynamic simulation tools, EnergyPlus and DesignBuilder. The life cycle energy consumption and CO2 emissions of various measures have been calculated. Optimum alternatives have been proposed in the temperate-dry climatic zones of Turkey.